2017
DOI: 10.1017/s1751731116001646
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between milks differentiated on native milk fat globule characteristics and fat, protein and calcium compositions

Abstract: Many studies have shown that milk fat globule (MFG) diameter varies in dairy cows in relation to diet and/or breed. However, the mechanisms governing the size of the fat globules remain hypothetical. Our objective was to determine the variable biochemical characteristics (fat, protein, fatty acids (FA), casein and calcium (Ca) contents) between individual milk which differed in both MFG diameter and membrane content, in order to speculate about the links between milk synthesis and MFG secretion. With this aim,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
6
19
0
Order By: Relevance
“…Smaller MFG have previously been associated with a decrease in fat content (Hurtaud et al 2010). The decrease in milk fat content would induce synthesis of smaller MFG, as also reported by Couvreur & Hurtaud (2017). ALG and SEL/ALG also increased initial FFA and SL, expressed in mEq/100 g of fat, compared to CTRL.…”
Section: Discussionsupporting
confidence: 70%
“…Smaller MFG have previously been associated with a decrease in fat content (Hurtaud et al 2010). The decrease in milk fat content would induce synthesis of smaller MFG, as also reported by Couvreur & Hurtaud (2017). ALG and SEL/ALG also increased initial FFA and SL, expressed in mEq/100 g of fat, compared to CTRL.…”
Section: Discussionsupporting
confidence: 70%
“…Although, the TG classes measured in this study were limited to species with CN ≥ 48, these results align with the results reported by others 14 . Therefore, the results of the milk lipidome in combinations with previously reported results 14,18 , indicate higher saturation in LMFG cows compared to SMFG cows, while fat yield and fat content were statistically similar between the groups (Table 1).…”
supporting
confidence: 75%
“…To a lesser extent, the size of fat globules, which is influenced by fatty acid composition (Timmen and Patton, 1988;Couvreur and Hurtaud, 2017), is also associated with milk coagulation via their interaction with the aggregation of casein micelles. However, results have not always been consistent.…”
Section: Genetic Correlations Between Cmp and Milk Compositionmentioning
confidence: 99%